2008
DOI: 10.1158/0008-5472.can-07-6460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypoxia-Inducible Factor-1α as a Novel Target for miR-17-92 MicroRNA Cluster

Abstract: MicroRNAs (miRNAs) are a distinct class of small noncoding RNAs that posttranscriptionally repress expression of target genes through imperfect base pairing with the 3 ¶ untranslated region. We previously reported amplification and overexpression of the miR-17-92 miRNA cluster at 13q31.3 in lung cancers, as well as growth inhibition by treatment with antisense oligonucleotides against miR-17-5p and miR-20a, constituents of miR-17-92, specifically in miR-17-92-overexpressing lung cancer cell lines. Although the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(201 citation statements)
references
References 19 publications
8
193
0
Order By: Relevance
“…Dicer-dependent generation of miR-185, was found to target HIF-2α transcripts. In addition, miR-17-92 cluster regulates HIF-1α via c-myc (20). A recent study demonstrated an intricate relationship between miR-20a, HIF-1α, and c-Myc (21).…”
Section: Discussionmentioning
confidence: 99%
“…Dicer-dependent generation of miR-185, was found to target HIF-2α transcripts. In addition, miR-17-92 cluster regulates HIF-1α via c-myc (20). A recent study demonstrated an intricate relationship between miR-20a, HIF-1α, and c-Myc (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-17-92 is included in the c-myc-mediated repression of hypoxia-inducible factor1a (HIF-1a). 8 HIF-1a plays a role in cell proliferation during hypoxia, and its upregulation in CLL bone marrow biopsies was linked with microvessel proliferation. Interestingly, other hypoxia-associated miRNA family miR-23 has a higher expression in the unmutated IgV H samples (Figures 2c and d).…”
Section: Letters To the Editormentioning
confidence: 97%
“…117 Second, they also target the VEGF transcription factor, HIF-1a. 123,124 Third, these miRNAs are reported to regulate VEGF-mediated endothelial cell migration via the MEK/MAPK pathway. 125 Cancer cells exploit miRNA regulation of angiogenesis and promote tumor growth by downregulating VEGF-targeting miRNAs (miR-17, -20, -199a and -125b), 118,121 tipping the scale towards conditions favoring angiogenesis.…”
Section: Microrna Regulation Of Angiogenesismentioning
confidence: 99%